Application of FACTS devices for ATC enhancement in competitive power market / K.Radha Rani and J. Amarnath - Rani, K. Radha; Amarnath, J. (UiTM Press, 2010)
With the recent trends towards deregulating power systems around the world, transfer capability computation emerges as the key issue to a smoothly running power market with multiple transactions. In deregulated power systems, Available Transfer Capability analysis is presently a critical issue. This paper presents the calculation of ATC using DC and AC distribution factors. Flexible AC transmission system devices can be alternative to reduce the flows in heavily loaded lines, resulting in an increased transfer capability, low system loss, improved stability of the network and reduced cost of production by controlling the power flows in the network. Two types of FACTS are used in this study namely Thyristor Controlled Series Capacitor( and Unified Power Flow Controller for enhancing the available transfer capability of the interconnected power system. The ATC is computed for different transactions of IEEE 24-bus (single area) system.